Banking Sector Development, Inflation and Economic Growth of Pakistan: The Nexus - Awais, Muhammad; Ahmad, Sayed Fayaz; Riaz, Poonam; Ibrahim, Muhammad (The journal of contemporary issues in business and government, 2021)
Study has been conducted to analyze the causal relation among banking sector development, inflation and economic growth of Pakistan. Study undertake the yearly data from 1960 to 2018 where as data has been collected from world bank indicators. Banking sector development has been analyzed with help of five different variables BRM, CLP, DCP, DCB and BSI where as Inflation has been measure with help of inflation and economic development has been measure with GDP growth in percentage. Intiallyunitroot test has been applied on as collected data is in time series where GDP is found stationary at level I(0) and other avriables found stationary after taking first difference I(1).Johansson co-intergration test has been applied to identify the relationship between variables VECM granger causality test has been applied to identify the direction of relationship between variables. Results shows thatBidirectional causality found between INF and BRM while unidirectional causality found from GDP to INF, INF to GDP, GDP to CLP, INF to BSI, CLP to INF and INF to DCB Study conclude that not all the variables are integrated with eachother only few of selected variables of banking sectors have relation with GDP and INF.